Ceramic tile with metal wire drawing effect and preparation method thereof

By adopting specific formulas and metal brushing treatment technology in ceramic tiles, the limitations of traditional ceramic tiles in terms of corrosion resistance and decorative effects are solved, and the combination of high corrosion resistance and metal texture is achieved, which enhances the market competitiveness of ceramic tiles.

CN119430856AInactive Publication Date: 2025-02-14FOSHAN TUOBO BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411825425.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional ceramic tiles have limitations in corrosion resistance and decorative effects, which are difficult to meet the application needs in high corrosion resistance environments, and lack metal texture and dynamic light and shadow effects, which limits their competitiveness in the high-end decoration market.

Method used

Use specific formulas of ceramic tile blanks and glaze, including corrosion-resistant agents, rare earth element oxides and nano-silica, and use metal brushing treatment technology to form ceramic tiles with metal brushing effect.

Benefits of technology

It improves the corrosion resistance and hardness of ceramic tiles, enhances its application ability in high corrosion resistance environments, and improves the aesthetics and design sense of ceramic tiles through metal brushing effects, meeting the needs of the high-end decoration market.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a ceramic tile with a metal wire drawing effect and a preparation method thereof. According to the anti-corrosion ceramic tile, zirconium oxide, aluminum oxide and other components in the anti-corrosion agent can improve the resistance of the surface of the ceramic tile to acid, alkali and other chemical substances, so that the ceramic tile is not prone to corrosion or damage when making contact with kitchen seasonings, cleaning agents and other chemicals. By adding the nano silicon dioxide and the silicate filler, the hardness and the wear resistance of the surface of the ceramic tile are improved, so that the ceramic tile is more durable in daily use and is not easy to generate scratches. The rare earth element oxide and other components can improve the physical properties of the ceramic tile and enhance the strength and toughness, thereby prolonging the overall service life of the ceramic tile. By enhancing the corrosion resistance, the ceramic tile is suitable for more environments, such as commercial kitchens, laboratories, hospitals and other places with higher requirements on the corrosion resistance of materials. The ceramic tile with excellent corrosion resistance can meet the requirement of a higher standard, the market competitiveness of the product is enhanced, and more consumers are attracted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a ceramic tile with a metal wire drawing effect and a preparation method thereof. Background Art

[0002] As a common building decoration material, ceramic tiles are widely used in various buildings and indoor and outdoor decorations due to their beautiful appearance, durability and easy cleaning. However, traditional ceramic tiles have certain limitations in terms of corrosion resistance and decorative effect, which restricts their application in certain special environments. In existing technologies, the corrosion resistance of ceramic tiles mainly depends on the chemical composition and structure of their glaze.

[0003] However, traditional glaze formulas often cannot meet the requirements of environments with high corrosion resistance, such as kitchens, bathrooms, laboratories, etc. In these environments, tiles are easily affected by acid and alkali erosion, wear and water vapor, resulting in surface damage, thereby reducing their aesthetics and service life. At the same time, traditional tile decoration methods, such as printing and glaze spraying, can provide certain visual effects, but cannot achieve metallic texture and dynamic light and shadow effects, which limits the competitiveness of tiles in the high-end decoration market. Summary of the invention

[0004] The object of the present invention is to provide a ceramic tile with a metal brushed effect and a preparation method thereof in order to solve the above-mentioned problem.

[0005] The technical solution adopted by the present invention is as follows: A ceramic tile with a metal brushed effect, comprising:

[0006] Ceramic tile blank:

[0007] Porcelain clay (kaolin): 50-60 parts by weight

[0008] Quartz: 20-30 parts by weight

[0009] Feldspar: 15-20 parts by weight

[0010] Alumina (Al2O3): 5-10 parts by weight

[0011] Zirconium oxide (ZrO2): 5 to 10 parts by weight

[0012] Magnesium silicate (MgSiO3): 3-5 parts by weight

[0013] Rare earth element oxide (such as lanthanum oxide La2O3): 2 to 4 parts by weight;

[0014] Corrosion resistance agent: 5-10 parts by weight;

[0015] Glaze:

[0016] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5-10 parts by weight;

[0017] Silane coupling agent: 3 to 5 parts by weight;

[0018] Nano silicon dioxide (SiO2): 2 to 5 parts by weight

[0019] In a preferred embodiment, the method comprises the following steps:

[0020] S1: First, weigh the raw materials for preparing tiles according to the preparation formula;

[0021] Tile blank formula:

[0022] Porcelain clay (kaolin): 50-60 parts by weight

[0023] Quartz: 20-30 parts by weight

[0024] Feldspar: 15-20 parts by weight

[0025] Alumina (Al2O3): 5-10 parts by weight

[0026] Zirconium oxide (ZrO2): 5 to 10 parts by weight

[0027] Magnesium silicate (MgSiO3): 3-5 parts by weight

[0028] Rare earth element oxide (such as lanthanum oxide La2O3): 2 to 4 parts by weight;

[0029] Corrosion resistance agent: 5-10 parts by weight;

[0030] Glaze recipe:

[0031] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5-10 parts by weight;

[0032] Silane coupling agent: 3 to 5 parts by weight;

[0033] Nano silicon dioxide (SiO2): 2 to 5 parts by weight;

[0034] S2: Mix china clay, quartz, feldspar, alumina, zirconium oxide, magnesium silicate and rare earth element oxides in the above proportions. Use a ball mill to mix for at least 24 hours to ensure that the raw materials are fully mixed and have uniform fineness;

[0035] S3: sending the mixed slurry into a spray drying tower to obtain a powdery material;

[0036] S4: Pressing the powdered material into a ceramic tile blank;

[0037] S5: Dry the pressed tile blank to a suitable moisture content;

[0038] S6: Prepare the glaze, mix the base glaze with the organosilane waterproofing agent, silane coupling agent and nano-silica. Use a blender to stir for at least 1 hour to ensure that the additives in the glaze are evenly dispersed;

[0039] S7: Apply the mixed glaze evenly on the dried tile blank;

[0040] S8: Send the glazed ceramic tile blank into the kiln for firing. The firing temperature and time are: 1200-1250℃, and the duration is about 1-2 hours;

[0041] S9: The tiles are cooled naturally or forcedly in the kiln to prevent the tiles from cracking due to excessive temperature differences;

[0042] S10: Perform metal wire drawing on the cooled ceramic tile surface, using professional wire drawing equipment, adjusting the appropriate speed and strength to form a metal wire drawing effect on the ceramic tile surface;

[0043] S11: Inspection and packaging The ceramic tiles with qualified metal brushed effect are inspected for appearance, size, flatness, etc. After passing the inspection, they are packaged and prepared for sale, after which the entire ceramic tiles with metal brushed effect and their preparation process are completed.

[0044] In a preferred embodiment, in step S1, the corrosion resistant agent component is:

[0045] Zirconium oxide (ZrO2): 25wt%

[0046] Alumina (Al2O3): 20wt%

[0047] Magnesium silicate (MgSiO3): 15wt%

[0048] Rare earth element oxide (lanthanum oxide La2O3): 10wt%

[0049] Titanium oxide (TiO2): 5wt%

[0050] Silicon oxide (SiO2): 10wt%

[0051] Chromium oxide (Cr2O3): 5wt%

[0052] Cobalt oxide (CoO): 3wt%

[0053] Nickel oxide (NiO): 3wt%

[0054] Calcium silicate CaSiO3: 5wt%

[0055] Organic silane coupling agent: 2wt%

[0056] Nano-silicon dioxide (SiO2 nanoparticles): 5wt%;

[0057] The preparation method of the corrosion resistant agent is as follows: First, various inorganic powder components such as zirconium oxide, aluminum oxide, magnesium silicate, rare earth element oxides, titanium oxide, chromium oxide, cobalt oxide, nickel oxide and silicate fillers are accurately weighed according to the formula ratio and placed in a high-speed mixer for pre-mixing. Subsequently, nano-silicon dioxide is added to enhance the wear resistance and adhesion of the coating. Next, an organic silane coupling agent is gradually added during the mixing process to promote the chemical bonding of the filler to the surface of the tile. After the mixing is completed, the mixture is finely ground to ensure that all ingredients are evenly dispersed at the nanometer level. Finally, a high-pressure homogenizer is used for homogenization to obtain a stable suspension or paste-like corrosion resistant agent, which can be used for the surface treatment of tiles.

[0058] In a preferred embodiment, in step S2, when mixing the raw materials in the ball mill, the speed of the ball mill is controlled at 60-80 revolutions per minute, and zirconium oxide balls are used as grinding media with a size in the range of 0.5-1.0 mm. During the ball milling process, the ratio of raw materials to water is controlled at 1:1.5 to 1:2.0 to maintain proper fluidity of the slurry. The ball milling time is at least 24 hours, during which the fineness and uniformity of the slurry are regularly checked, and sieving is performed to remove oversized particles if necessary;

[0059] In step S3, the operating parameters of the spray drying tower include controlling the inlet temperature at 200-250°C and the outlet temperature at 100-150°C. The speed of the atomizer is adjusted according to the viscosity of the slurry to obtain uniform droplets. The moisture content of the dried powdered material is controlled within 6% to 8% to ensure suitable plasticity during pressing.

[0060] In a preferred embodiment, in step S4, the pressing of the tile blank is carried out on a hydraulic press, the pressure is controlled at 200-300 tons, and the pressure is maintained for about 30-60 seconds to ensure the density and dimensional stability of the blank. The thickness of the blank after pressing is controlled at 6-10 mm;

[0061] In step S5, the drying process is carried out in a tunnel dryer, the temperature is controlled at 100-120° C., the relative humidity is controlled at 55%-65%, and the drying time is about 6-8 hours, so that the moisture content of the green body is reduced to 2%-4%.

[0062] In a preferred embodiment, in step S6, when preparing the glaze, a high-speed stirrer is used with a rotation speed of 1000-1500 rpm to ensure that the organosilane water repellent, the silane coupling agent and the nano-silicon dioxide can be evenly dispersed in the base glaze. The stirring time is at least 1 hour, and the uniformity of the glaze is regularly checked during the stirring time.

[0063] In a preferred embodiment, in step S7, when applying the glaze, an automatic glazing machine is used, and the thickness of the glaze layer is controlled to be 0.5-1.0 mm. During the glazing process, the ceramic tile blank is kept moving smoothly to avoid glaze accumulation or dripping.

[0064] In a preferred embodiment, in step S8, during the firing process, the heating rate of the kiln is controlled at 5-10°C / min, and the firing temperature is maintained for 1-2 hours after reaching the firing temperature. Accurate control of the firing temperature is crucial to ensure the strength and glaze quality of the tiles.

[0065] In a preferred embodiment, in step S9, the cooling process is performed slowly to avoid thermal cracking of the tiles. The rate of natural cooling or forced cooling is controlled at 20-30°C / hour until the temperature of the tiles drops below 100°C.

[0066] In a preferred embodiment, in step S10, during the metal wire drawing process, the wire drawing equipment has a line speed of 10-15 meters per minute, and the strength is adjusted according to the hardness of the tile surface to form a uniform metal wire drawing texture. The wire drawing direction and texture depth are adjusted according to design requirements;

[0067] In step S11, during the inspection process, the appearance, size and flatness of the tiles are inspected using precision measuring tools and instruments. The appearance inspection is carried out under good lighting conditions, and the size error is controlled within ±1 mm, and the flatness error is less than 0.5 mm. Qualified products are packaged in foam packaging and cartons to ensure safety during transportation.

[0068] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0069] 1. In the present invention, zirconium oxide, aluminum oxide and other ingredients in the corrosion resistance agent can improve the resistance of the ceramic tile surface to chemical substances such as acids and alkalis, so that the ceramic tile is not easily corroded or damaged when it comes into contact with chemicals such as kitchen condiments and detergents. The addition of nano-silicon dioxide and silicate fillers improves the hardness and wear resistance of the ceramic tile surface, making the ceramic tile more durable and less prone to scratches in daily use. Ingredients such as rare earth element oxides can improve the physical properties of ceramic tiles, increase their strength and toughness, and thus increase the overall service life of the ceramic tile. By enhancing the corrosion resistance, ceramic tiles are suitable for more environments, such as commercial kitchens, laboratories, hospitals and other places that have high requirements for material corrosion resistance. Ceramics with excellent corrosion resistance can meet higher standards, enhance the market competitiveness of products, and attract more consumers.

[0070] 2. In the present invention, the metal brushed effect provides a unique metallic luster and texture for the surface of the tile, enhances the aesthetics and design of the product, and meets the consumer's demand for personalized and high-end decorative materials. The metal brushed texture can reflect light, so that the surface of the tile produces a dynamic light and shadow effect, which enhances the decorative effect and layering of the space. As a special process, metal brushing can significantly increase the added value of tiles and bring higher economic benefits to manufacturers. The metal brushed texture can cover up minor flaws on the surface of the tile to a certain extent, making the product look more perfect as a whole. Through different brushing speeds, strengths and directions, a variety of metal brushed effects can be created, providing the market with a variety of product choices. DETAILED DESCRIPTION

[0071] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0072] Embodiment 1:

[0073] A ceramic tile with a metal brushed effect, comprising:

[0074] Ceramic tile blank:

[0075] Porcelain clay (kaolin): 50 parts by weight

[0076] Quartz: 20 parts by weight

[0077] Feldspar: 15 parts by weight

[0078] Alumina (Al2O3): 5 parts by weight

[0079] Zirconium oxide (ZrO2): 5 parts by weight

[0080] Magnesium silicate (MgSiO3): 3 parts by weight

[0081] Rare earth element oxide (such as lanthanum oxide La2O3): 2 parts by weight;

[0082] Anticorrosive agent: 5 parts by weight;

[0083] Glaze:

[0084] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5 parts by weight;

[0085] Silane coupling agent: 3 parts by weight;

[0086] Nano silicon dioxide (SiO2): 2 parts by weight.

[0087] The method comprises the following steps:

[0088] S1: First, weigh the raw materials for preparing tiles according to the preparation formula;

[0089] Tile blank formula:

[0090] Porcelain clay (kaolin): 50 parts by weight

[0091] Quartz: 20 parts by weight

[0092] Feldspar: 15 parts by weight

[0093] Alumina (Al2O3): 5 parts by weight

[0094] Zirconium oxide (ZrO2): 5 parts by weight

[0095] Magnesium silicate (MgSiO3): 3 parts by weight

[0096] Rare earth element oxide (such as lanthanum oxide La2O3): 2 parts by weight;

[0097] Anticorrosive agent: 5 parts by weight;

[0098] Glaze:

[0099] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5 parts by weight;

[0100] Silane coupling agent: 3 parts by weight;

[0101] Nano silicon dioxide (SiO2): 2 parts by weight;

[0102] S2: Mix china clay, quartz, feldspar, alumina, zirconium oxide, magnesium silicate and rare earth element oxides in the above proportions. Use a ball mill to mix for at least 24 hours to ensure that the raw materials are fully mixed and have uniform fineness;

[0103] S3: sending the mixed slurry into a spray drying tower to obtain a powdery material;

[0104] S4: Pressing the powdered material into a ceramic tile blank;

[0105] S5: Dry the pressed tile blank to a suitable moisture content;

[0106] S6: Prepare the glaze, mix the base glaze with the organosilane waterproofing agent, silane coupling agent and nano-silica. Use a blender to stir for at least 1 hour to ensure that the additives in the glaze are evenly dispersed;

[0107] S7: Apply the mixed glaze evenly on the dried tile blank;

[0108] S8: Send the glazed ceramic tile blank into the kiln for firing. The firing temperature and time are: 1200-1250℃, and the duration is about 1-2 hours;

[0109] S9: The tiles are cooled naturally or forcedly in the kiln to prevent the tiles from cracking due to excessive temperature differences;

[0110] S10: Perform metal wire drawing on the cooled ceramic tile surface, using professional wire drawing equipment, adjusting the appropriate speed and strength to form a metal wire drawing effect on the ceramic tile surface;

[0111] S11: Inspection and packaging The ceramic tiles with qualified metal brushed effect are inspected for appearance, size, flatness, etc. After passing the inspection, they are packaged and prepared for sale, after which the entire ceramic tiles with metal brushed effect and their preparation process are completed.

[0112] In step S1, the corrosion resistance agent composition is:

[0113] Zirconium oxide (ZrO2): 25wt%

[0114] Alumina (Al2O3): 20wt%

[0115] Magnesium silicate (MgSiO3): 15wt%

[0116] Rare earth element oxide (lanthanum oxide La2O3): 10wt%

[0117] Titanium oxide (TiO2): 5wt%

[0118] Silicon oxide (SiO2): 10wt%

[0119] Chromium oxide (Cr2O3): 5wt%

[0120] Cobalt oxide (CoO): 3wt%

[0121] Nickel oxide (NiO): 3wt%

[0122] Calcium silicate CaSiO3: 5wt%

[0123] Organic silane coupling agent: 2wt%

[0124] Nano-silicon dioxide (SiO2 nanoparticles): 5wt%;

[0125] The preparation method of the corrosion resistant agent is as follows: First, various inorganic powder components such as zirconium oxide, aluminum oxide, magnesium silicate, rare earth element oxides, titanium oxide, chromium oxide, cobalt oxide, nickel oxide and silicate fillers are accurately weighed according to the formula ratio and placed in a high-speed mixer for pre-mixing. Subsequently, nano-silicon dioxide is added to enhance the wear resistance and adhesion of the coating. Next, an organic silane coupling agent is gradually added during the mixing process to promote the chemical bonding of the filler to the surface of the tile. After the mixing is completed, the mixture is finely ground to ensure that all ingredients are evenly dispersed at the nanometer level. Finally, a high-pressure homogenizer is used for homogenization to obtain a stable suspension or paste-like corrosion resistant agent, which can be used for the surface treatment of tiles.

[0126] In step S2, when mixing the raw materials in the ball mill, the speed of the ball mill should be controlled at 60-80 revolutions per minute, and zirconium oxide balls are used as grinding media, and their size should be in the range of 0.5-1.0 mm. During the ball milling process, the ratio of raw materials to water should be controlled at 1:1.5 to 1:2.0 to maintain proper fluidity of the slurry. The ball milling time is at least 24 hours, during which the fineness and uniformity of the slurry are regularly checked, and sieving is performed to remove oversized particles if necessary;

[0127] In step S3, the operating parameters of the spray drying tower include the inlet temperature being controlled at 200-250°C and the outlet temperature being between 100-150°C. The speed of the atomizer should be adjusted according to the viscosity of the slurry to obtain uniform droplets. The moisture content of the dried powdered material should be controlled within 6% to 8% to ensure suitable plasticity during pressing.

[0128] In step S4, the pressing of the tile blank should be carried out on a hydraulic press, with the pressure controlled at 200-300 tons and the pressure maintained for about 30-60 seconds to ensure the density and dimensional stability of the blank. The thickness of the blank after pressing should be controlled at 6-10 mm;

[0129] In step S5, the drying process should be carried out in a tunnel dryer, with the temperature controlled at 100-120°C, the relative humidity controlled at 55%-65%, and the drying time being about 6-8 hours, so as to reduce the moisture content of the green body to 2%-4%.

[0130] In step S6, when preparing the glaze, a high-speed stirrer is used, and the rotation speed should reach 1000-1500 rpm to ensure that the organosilane water repellent, silane coupling agent and nano-silicon dioxide can be evenly dispersed in the base glaze. The stirring time is at least 1 hour, and the uniformity of the glaze is regularly checked during this period.

[0131] In step S7, when applying the glaze, an automatic glazing machine is used, and the thickness of the glaze layer is controlled to be 0.5-1.0 mm. During the glazing process, the ceramic tile blank should be kept moving smoothly to avoid glaze accumulation or dripping.

[0132] In step S8, during the firing process, the heating rate of the kiln should be controlled at 5-10°C / minute, and the firing temperature should be maintained for 1-2 hours after reaching the firing temperature. Accurate control of the firing temperature is crucial to ensure the strength and glaze quality of the tiles.

[0133] In step S9, the cooling process should be carried out slowly to avoid cracking of the tiles caused by thermal stress. The rate of natural cooling or forced cooling should be controlled at 20-30°C / hour until the temperature of the tiles drops below 100°C.

[0134] In step S10, during the metal wire drawing process, the wire drawing equipment's linear speed should be controlled at 10-15 meters per minute, and the strength should be adjusted according to the hardness of the tile surface to form a uniform metal wire drawing texture. The wire drawing direction and texture depth should be adjusted according to the design requirements;

[0135] In step S11, during the inspection process, the appearance, size and flatness of the tiles are inspected using precision measuring tools and instruments. The appearance inspection should be carried out under good lighting conditions, the size error should be controlled within ±1 mm, and the flatness error should be less than 0.5 mm. Qualified products are packaged in foam packaging and cartons to ensure safety during transportation.

[0136] In the present invention, zirconium oxide, aluminum oxide and other components in the corrosion resistance agent can improve the resistance of the ceramic tile surface to chemical substances such as acids and alkalis, so that the ceramic tile is not easily corroded or damaged when it comes into contact with chemicals such as kitchen condiments and detergents. The addition of nano-silicon dioxide and silicate fillers improves the hardness and wear resistance of the ceramic tile surface, making the ceramic tile more durable and less prone to scratches in daily use. Ingredients such as rare earth element oxides can improve the physical properties of the ceramic tile, increase its strength and toughness, and thus increase the overall service life of the ceramic tile. By enhancing the corrosion resistance, the ceramic tile is suitable for more environments, such as commercial kitchens, laboratories, hospitals and other places that have high requirements for the corrosion resistance of the material. Ceramic tiles with excellent corrosion resistance can meet higher standards, enhance the market competitiveness of the product, and attract more consumers.

[0137] In the present invention, the metal brushed effect provides a unique metallic luster and texture for the surface of the tile, enhances the aesthetics and design of the product, and meets the consumer's demand for personalized and high-end decorative materials. The metal brushed texture can reflect light, so that the surface of the tile produces a dynamic light and shadow effect, which enhances the decorative effect and layering of the space. As a special process, metal brushing treatment can significantly increase the added value of the tile and bring higher economic benefits to manufacturers. The metal brushed texture can cover up minor flaws on the surface of the tile to a certain extent, making the product look more perfect as a whole. Through different brushing speeds, strengths and directions, a variety of metal brushed effects can be created, providing the market with a variety of product choices.

[0138] Embodiment 2:

[0139] A ceramic tile with a metal brushed effect, comprising:

[0140] Ceramic tile blank:

[0141] China clay (kaolin): 60 parts by weight

[0142] Quartz: 0 parts by weight

[0143] Feldspar: 120 parts by weight

[0144] Alumina (Al2O3): 10 parts by weight

[0145] Zirconium oxide (ZrO2): 10 parts by weight

[0146] Magnesium silicate (MgSiO3): 5 parts by weight

[0147] Rare earth element oxide (such as lanthanum oxide La2O3): 4 parts by weight;

[0148] Corrosion resistance agent: 10 parts by weight;

[0149] Glaze:

[0150] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 100 parts by weight Organosilane waterproofing agent: 10 parts by weight;

[0151] Silane coupling agent: 5 parts by weight;

[0152] Nano silicon dioxide (SiO2): 5 parts by weight.

[0153] The method comprises the following steps:

[0154] S1: First, weigh the raw materials for preparing tiles according to the preparation formula;

[0155] Tile blank formula:

[0156] Ceramic tile blank:

[0157] China clay (kaolin): 60 parts by weight

[0158] Quartz: 0 parts by weight

[0159] Feldspar: 120 parts by weight

[0160] Alumina (Al2O3): 10 parts by weight

[0161] Zirconium oxide (ZrO2): 10 parts by weight

[0162] Magnesium silicate (MgSiO3): 5 parts by weight

[0163] Rare earth element oxide (such as lanthanum oxide La2O3): 4 parts by weight;

[0164] Corrosion resistance agent: 10 parts by weight;

[0165] Glaze:

[0166] Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 100 parts by weight Organosilane waterproofing agent: 10 parts by weight;

[0167] Silane coupling agent: 5 parts by weight;

[0168] Nano silicon dioxide (SiO2): 5 parts by weight;

[0169] S2: Mix china clay, quartz, feldspar, alumina, zirconium oxide, magnesium silicate and rare earth element oxides in the above proportions. Use a ball mill to mix for at least 24 hours to ensure that the raw materials are fully mixed and have uniform fineness;

[0170] S3: sending the mixed slurry into a spray drying tower to obtain a powdery material;

[0171] S4: Pressing the powdered material into a ceramic tile blank;

[0172] S5: Dry the pressed tile blank to a suitable moisture content;

[0173] S6: Prepare the glaze, mix the base glaze with the organosilane waterproofing agent, silane coupling agent and nano-silica. Use a blender to stir for at least 1 hour to ensure that the additives in the glaze are evenly dispersed;

[0174] S7: Apply the mixed glaze evenly on the dried tile blank;

[0175] S8: Send the glazed ceramic tile blank into the kiln for firing. The firing temperature and time are: 1200-1250℃, and the duration is about 1-2 hours;

[0176] S9: The tiles are cooled naturally or forcedly in the kiln to prevent the tiles from cracking due to excessive temperature differences;

[0177] S10: Perform metal wire drawing on the cooled ceramic tile surface, using professional wire drawing equipment, adjusting the appropriate speed and strength to form a metal wire drawing effect on the ceramic tile surface;

[0178] S11: Inspection and packaging The ceramic tiles with qualified metal brushed effect are inspected for appearance, size, flatness, etc. After passing the inspection, they are packaged and prepared for sale, after which the entire ceramic tiles with metal brushed effect and their preparation process are completed.

[0179] In step S1, the corrosion resistance agent composition is:

[0180] Zirconium oxide (ZrO2): 25wt%

[0181] Alumina (Al2O3): 20wt%

[0182] Magnesium silicate (MgSiO3): 15wt%

[0183] Rare earth element oxide (lanthanum oxide La2O3): 10wt%

[0184] Titanium oxide (TiO2): 5wt%

[0185] Silicon oxide (SiO2): 10wt%

[0186] Chromium oxide (Cr2O3): 5wt%

[0187] Cobalt oxide (CoO): 3wt%

[0188] Nickel oxide (NiO): 3wt%

[0189] Calcium silicate CaSiO3: 5wt%

[0190] Organic silane coupling agent: 2wt%

[0191] Nano-silicon dioxide (SiO2 nanoparticles): 5wt%;

[0192] The preparation method of the corrosion resistant agent is as follows: First, various inorganic powder components such as zirconium oxide, aluminum oxide, magnesium silicate, rare earth element oxides, titanium oxide, chromium oxide, cobalt oxide, nickel oxide and silicate fillers are accurately weighed according to the formula ratio and placed in a high-speed mixer for pre-mixing. Subsequently, nano-silicon dioxide is added to enhance the wear resistance and adhesion of the coating. Next, an organic silane coupling agent is gradually added during the mixing process to promote the chemical bonding of the filler to the surface of the tile. After the mixing is completed, the mixture is finely ground to ensure that all ingredients are evenly dispersed at the nanometer level. Finally, a high-pressure homogenizer is used for homogenization to obtain a stable suspension or paste-like corrosion resistant agent, which can be used for the surface treatment of tiles.

[0193] In step S2, when mixing the raw materials in the ball mill, the speed of the ball mill should be controlled at 60-80 revolutions per minute, and zirconium oxide balls are used as grinding media, and their size should be in the range of 0.5-1.0 mm. During the ball milling process, the ratio of raw materials to water should be controlled at 1:1.5 to 1:2.0 to maintain proper fluidity of the slurry. The ball milling time is at least 24 hours, during which the fineness and uniformity of the slurry are regularly checked, and sieving is performed to remove oversized particles if necessary;

[0194] In step S3, the operating parameters of the spray drying tower include the inlet temperature being controlled at 200-250°C and the outlet temperature being between 100-150°C. The speed of the atomizer should be adjusted according to the viscosity of the slurry to obtain uniform droplets. The moisture content of the dried powdered material should be controlled within 6% to 8% to ensure suitable plasticity during pressing.

[0195] In step S4, the pressing of the tile blank should be carried out on a hydraulic press, with the pressure controlled at 200-300 tons and the pressure maintained for about 30-60 seconds to ensure the density and dimensional stability of the blank. The thickness of the blank after pressing should be controlled at 6-10 mm;

[0196] In step S5, the drying process should be carried out in a tunnel dryer, with the temperature controlled at 100-120°C, the relative humidity controlled at 55%-65%, and the drying time being about 6-8 hours, so as to reduce the moisture content of the green body to 2%-4%.

[0197] In step S6, when preparing the glaze, a high-speed stirrer is used, and the rotation speed should reach 1000-1500 rpm to ensure that the organosilane water repellent, silane coupling agent and nano-silicon dioxide can be evenly dispersed in the base glaze. The stirring time is at least 1 hour, and the uniformity of the glaze is regularly checked during this period.

[0198] In step S7, when applying the glaze, an automatic glazing machine is used, and the thickness of the glaze layer is controlled to be 0.5-1.0 mm. During the glazing process, the ceramic tile blank should be kept moving smoothly to avoid glaze accumulation or dripping.

[0199] In step S8, during the firing process, the heating rate of the kiln should be controlled at 5-10°C / minute, and the firing temperature should be maintained for 1-2 hours after reaching the firing temperature. Accurate control of the firing temperature is crucial to ensure the strength and glaze quality of the tiles.

[0200] In step S9, the cooling process should be carried out slowly to avoid cracking of the tiles caused by thermal stress. The rate of natural cooling or forced cooling should be controlled at 20-30°C / hour until the temperature of the tiles drops below 100°C.

[0201] In step S10, during the metal wire drawing process, the wire drawing equipment's linear speed should be controlled at 10-15 meters per minute, and the strength should be adjusted according to the hardness of the tile surface to form a uniform metal wire drawing texture. The wire drawing direction and texture depth should be adjusted according to the design requirements;

[0202] In step S11, during the inspection process, the appearance, size and flatness of the tiles are inspected using precision measuring tools and instruments. The appearance inspection should be carried out under good lighting conditions, the size error should be controlled within ±1 mm, and the flatness error should be less than 0.5 mm. Qualified products are packaged in foam packaging and cartons to ensure safety during transportation.

[0203] In the present invention, zirconium oxide, aluminum oxide and other components in the corrosion resistance agent can improve the resistance of the ceramic tile surface to chemical substances such as acids and alkalis, so that the ceramic tile is not easily corroded or damaged when it comes into contact with chemicals such as kitchen condiments and detergents. The addition of nano-silicon dioxide and silicate fillers improves the hardness and wear resistance of the ceramic tile surface, making the ceramic tile more durable and less prone to scratches in daily use. Ingredients such as rare earth element oxides can improve the physical properties of the ceramic tile, increase its strength and toughness, and thus increase the overall service life of the ceramic tile. By enhancing the corrosion resistance, the ceramic tile is suitable for more environments, such as commercial kitchens, laboratories, hospitals and other places that have high requirements for the corrosion resistance of the material. Ceramic tiles with excellent corrosion resistance can meet higher standards, enhance the market competitiveness of the product, and attract more consumers.

[0204] In the present invention, the metal brushed effect provides a unique metallic luster and texture for the surface of the tile, enhances the aesthetics and design of the product, and meets the consumer's demand for personalized and high-end decorative materials. The metal brushed texture can reflect light, so that the surface of the tile produces a dynamic light and shadow effect, which enhances the decorative effect and layering of the space. As a special process, metal brushing treatment can significantly increase the added value of the tile and bring higher economic benefits to manufacturers. The metal brushed texture can cover up minor flaws on the surface of the tile to a certain extent, making the product look more perfect as a whole. Through different brushing speeds, strengths and directions, a variety of metal brushed effects can be created, providing the market with a variety of product choices.

[0205] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0206] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic tile with a metal brushed effect, characterized in that: include: Ceramic tile blank: China clay (kaolin): 50-60 parts by weight; Quartz: 20-30 parts by weight; Feldspar: 15-20 parts by weight; Alumina (Al2O3): 5-10 parts by weight; Zirconium oxide (ZrO2): 5 to 10 parts by weight; Magnesium silicate (MgSiO3): 3 to 5 parts by weight; Rare earth element oxide (such as lanthanum oxide La2O3): 2 to 4 parts by weight; Corrosion resistance agent: 5-10 parts by weight; Glaze: Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5-10 parts by weight; Silane coupling agent: 3 to 5 parts by weight; Nano silicon dioxide (SiO2): 2 to 5 parts by weight.

2. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: The method comprises the following steps: S1: First, weigh the raw materials for preparing tiles according to the preparation formula; Tile blank formula: Porcelain clay (kaolin): 50-60 parts by weight Quartz: 20-30 parts by weight Feldspar: 15-20 parts by weight Alumina (Al2O3): 5-10 parts by weight Zirconium oxide (ZrO2): 5 to 10 parts by weight Magnesium silicate (MgSiO3): 3-5 parts by weight Rare earth element oxide (such as lanthanum oxide La2O3): 2 to 4 parts by weight; Corrosion resistance agent: 5-10 parts by weight; Glaze recipe: Basic glaze (including glaze raw materials such as strontium silicate, barium silicate, etc.): 90-100 parts by weight Organosilane waterproofing agent: 5-10 parts by weight; Silane coupling agent: 3 to 5 parts by weight; Nano silicon dioxide (SiO2): 2 to 5 parts by weight; S2: Mixing china clay, quartz, feldspar, alumina, zirconium oxide, magnesium silicate and rare earth element oxides in the above proportions; using a ball mill to mix for at least 24 hours to ensure that the raw materials are fully mixed and have uniform fineness; S3: sending the mixed slurry into a spray drying tower to obtain a powdery material; S4: Pressing the powdered material into a ceramic tile blank; S5: Dry the pressed tile blank to a suitable moisture content; S6: Prepare glaze, mix the base glaze with the organosilane waterproofing agent, the silane coupling agent and the nano-silica evenly; use a mixer to stir for at least 1 hour to ensure that the additives in the glaze are evenly dispersed; S7: Apply the mixed glaze evenly on the dried tile blank; S8: sending the glazed ceramic tile blank into the kiln for firing at a temperature and time of 1200-1250°C for 1-2 hours; S9: The tiles are cooled naturally or forcedly in the kiln to prevent the tiles from cracking due to excessive temperature difference; S10: Perform metal wire drawing on the cooled ceramic tile surface, using professional wire drawing equipment, adjusting the appropriate speed and strength to form a metal wire drawing effect on the ceramic tile surface; S11: Inspection and packaging The ceramic tiles with qualified metal brushed effect are inspected for appearance, size, flatness, etc. After passing the inspection, they are packaged and prepared for sale, after which the entire ceramic tiles with metal brushed effect and their preparation process are completed.

3. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S1, the corrosion resistant agent comprises: Zirconium oxide (ZrO2): 25wt%; Alumina (Al2O3): 20wt%; Magnesium silicate (MgSiO3): 15wt%; Rare earth element oxide (lanthanum oxide La2O3): 10wt%; Titanium oxide (TiO2): 5wt%; Silicon oxide (SiO2): 10wt%; Chromium oxide (Cr2O3): 5wt%; Cobalt oxide (CoO): 3wt%; Nickel oxide (NiO): 3wt%; Calcium silicate CaSiO3: 5wt%; Organic silane coupling agent: 2wt%; Nano-silicon dioxide (SiO2 nanoparticles): 5wt%; The preparation method of the corrosion resistant agent is as follows: first, various inorganic powder components such as zirconium oxide, aluminum oxide, magnesium silicate, rare earth element oxides, titanium oxide, chromium oxide, cobalt oxide, nickel oxide and silicate fillers are accurately weighed according to the formula ratio, and put into a high-speed mixer for pre-mixing; then, nano-silicon dioxide is added to enhance the wear resistance and adhesion of the coating; then, an organic silane coupling agent is gradually added during the mixing process to promote the chemical bonding between the filler and the surface of the tile; after the mixing is completed, the mixture is finely ground to ensure that all the ingredients are evenly dispersed at the nanometer level; finally, a high-pressure homogenizer is used for homogenization to obtain a stable suspension or paste-like corrosion resistant agent, which can be used for the surface treatment of the tile.

4. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In the step S2, when the raw materials are mixed in the ball mill, the rotation speed of the ball mill is controlled at 60-80 revolutions per minute, and zirconium oxide balls are used as grinding media, and the size of the balls is in the range of 0.5-1.0 mm; during the ball milling process, the ratio of the raw materials to water is controlled at 1:1.5 to 1:2.0 to maintain the proper fluidity of the slurry; the ball milling time is at least 24 hours, during which the fineness and uniformity of the slurry are regularly checked, and if necessary, sieving is performed to remove oversized particles; In step S3, the operating parameters of the spray drying tower include controlling the inlet temperature at 200-250°C and the outlet temperature at 100-150°C; adjusting the rotation speed of the atomizer according to the viscosity of the slurry to obtain uniform droplets; and controlling the moisture content of the dried powdered material within 6% to 8% to ensure suitable plasticity during pressing.

5. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S4, the ceramic tile blank is pressed on a hydraulic press, the pressure is controlled at 200-300 tons, and the pressure is maintained for 30-60 seconds to ensure the density and dimensional stability of the blank; the thickness of the blank after pressing is controlled at 6-10 mm; In step S5, the drying process is carried out in a tunnel dryer, the temperature is controlled at 100-120° C., the relative humidity is controlled at 55%-65%, and the drying time is 6-8 hours, so that the moisture content of the green body is reduced to 2%-4%.

6. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S6, when preparing the glaze, a high-speed stirrer is used with a rotation speed of 1000-1500 rpm to ensure that the organosilane water repellent, silane coupling agent and nano-silica can be evenly dispersed in the basic glaze; the stirring time is at least 1 hour, and the uniformity of the glaze is regularly checked during the stirring time.

7. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S7, when applying the glaze, an automatic glazing machine is used, and the thickness of the glaze layer is controlled to be 0.5-1.0 mm; during the glazing process, the ceramic tile blank is kept moving smoothly to avoid glaze accumulation or dripping.

8. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S8, during the firing process, the heating rate of the kiln is controlled at 5-10°C / minute, and the firing temperature is maintained for 1-2 hours after reaching the firing temperature; accurate control of the firing temperature is crucial to ensure the strength of the tile and the quality of the glaze.

9. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In step S9, the cooling process is carried out slowly to avoid cracking of the tiles caused by heat; the rate of natural cooling or forced cooling is controlled at 20-30°C / hour until the temperature of the tiles drops below 100°C.

10. A ceramic tile with a metal brushed effect and a method for preparing the same as claimed in claim 1, characterized in that: In the step S10, during the metal wire drawing process, the wire drawing equipment's linear speed is controlled at 10-15 meters per minute, and the strength is adjusted according to the hardness of the tile surface to form a uniform metal wire drawing texture; the wire drawing direction and texture depth are adjusted according to the design requirements; In the step S11, during the inspection process, the appearance, size and flatness of the tiles are inspected using precision measuring tools and instruments; the appearance inspection is carried out under good lighting conditions, the size error is controlled within ±1 mm, and the flatness error is less than 0.5 mm; Qualified products are packed with foam packaging and cartons to ensure safety during transportation.